Teaching Burnout: a conceptual cartographic review - Petrona Aguirre, Jimena Isabel; Marsollier, Roxana; Vecino, José (AWARI, 2020)
Burnout syndrome is a problem in healthcare workers in the field of health and education. From the 1970s to the present it has been the focus of growing interest in various research. The professional attrition of teachers, in particular, has been addressed in studies published in journals of scientific relevance, which highlights a phenomenon in the educational field that is of concern in different contexts. Conceptual cartographic diving is proposed in SciELO (Scientific Electronic Library Online) of the most cited articles related to teacher burnout. We work on theoretical categories that allow us to penetrate discussions about burnout in teaching through the use of the software QDA Miner 5 and WordStat 7. The analysis allows us to review psychosocial contributions regarding the syndrome in literature, feedback questions, and anticipate new concerns in relation to recent and impact investigations.